The role of microorganisms of the main ecological and trophic groups in the transfer of 137Cs from soddy-podzolic sandy loam soil into the biomass of Avena sativa L - Tankevich, Elena; Nikitin, Aleksander; Simonchyk, Yuliya; Kantsavaya, Irina (Journal of the Belarusian State University. Ecology, 2024)
In this work, we investigated the influence of soil microorganisms of the main ecological-trophic groups on the transition of cesium-137 from the soddy-podzolic sandy loam soil of the Chernobyl nuclear power plant exclusion zone into the biomass of oats (Avena sativa L.). Changes of K, Ca, Sr, Cs bioavailable forms, concentration in the soil under impact of these microorganisms investigated also.It has been established that the introduction of amylolytic bacteria and spore-forming ammonifiers into soddy-podzolic sandy loam soil enhances the translocation of 137Cs from the underground organs of oats to the aboveground ones by 1,8-4,3 times. At the same time, the radionuclide content in the underground organs of oats decreases by 29.5% when spore-forming ammonifiers are added to the soil. The introduction of the consortium of microorganisms EM-1 into the soddy-podzolic sandy loam soil reduced the accumulation of 137Cs in the above-ground organs of oats by 71,8%, while maintaining the level of radionuclide content in the root system. In an experimental system including soddy-podzolic sandy loam soil, oat plants and such physiological groups of microorganisms as amylolytic microorganisms or spore-forming ammonifiers, there is a significant increase in the content of 137Cs in water-soluble form by 1,5 and 3,5 times, respectively, which can explain the increase in accumulation radionuclide in above-ground plant organs.The introduction of the consortium of microorganisms EM-1 into the soddy-podzolic soil reduced the content of 137Cs in water-soluble form by 32,6%. Changes similar in direction are observed in relation to the water-soluble form of К: amylolytic microorganisms and spore-forming ammonifiers increase its concentration by 49,9% and 67,5%, respectively, and the microbiological preparation EM-1 reduces it by 52,9%.
Keywords: associations of soil microorganisms; radioactive contamination; exclusion zone of Chernobyl NPP; bioavailability of technogenic radionuclides; caesium-137; macroelements; microelements